The socio-cultural image of Tuvan officialdom in the XIX and XX centuries - Salimaa Khovalyg, Elena Aiyzhy, (Opción, 2019)
The purpose of the article is to study the socio-cultural image of Tuvan officialdom in the late XIX and early XX centuries. The methodological basis of the study is the principles of historicism, objectivism, and an integrated approach. As a result, since it is known that the effective functioning of the system of state power primarily depends on the people who carry out administrative activities, it is necessary to reconstruct the socio-cultural image of Tuvan officials. Analyzing the socio-cultural image of Tuvan officialdom, it can be concluded that a special social group has been formed in traditional Tuvan society.